Power generation and wastewater treatment using a novel SPEEK nanocomposite membrane in a dual chamber microbial fuel cell. (5th January 2015) - Ilbeygi, Hamid; Ghasemi, Mostafa; Emadzadeh, D.; Ismail, Ahmad Fauzi; Zaidi, S.M.J.; Aljlil, Saad A.; Jaafar, Juhana; Martin, Darren; Keshani, Samaneh
Abstract: In this paper, the performance of two common and two self-fabricated proton exchange membranes were compared. Nafion 112 and Nafion 117, which are two of the most common proton exchange membranes that can be used in all fuel cell systems, were compared to SPEEK and SP/CC/TAP. The results showed that at lower COD such as 2000 mg/l, Nafion 117 has the highest performance in terms of power production and COD removal, while once the COD of wastewater goes up to 5000 mg/l, SP/CC/TAP has approximately the same performance as Nafion 117. The membranes were characterized by FESEM, while the degree of sulfonation was measured by NMR. The oxidation activity of microorganisms was measure by cyclic voltammetry (CV). Also, the attachment of bacteria onto the anode electrode was observed by SEM, which showed that different bacteria from the media with a mixed culture inoculum had attached to the anode electrode. Highlights: Synthesizing of SPEEK/CC/TAP as a new PEM. Application of this new PEM in MFC. Evaluation of the performance of MFC with this PEM. Comparison of the results with Nafion 117 and Nafion 112 as the most common PEMs.